Bretherick's handbook of reactive chemical hazards - Bretherick, L. (Elsevier, 2017)
Bretherick's Handbook of Reactive Chemical Hazards, Eighth Edition presents the latest updates on the unexpected, but predictable, loss of containment and explosion hazards from chemicals and their admixtures and actual accidents. The extensively cross-referenced book enables readers to avoid explosion and loss of containment of chemicals. Primary and more specialized sources are easily traced, and this new edition includes available record updates, also adding a number of new records. In this newly updated and expanded edition, the content is presented in a clear and user-friendly format.
Previous edition: 2007.
Reactive Chemical Hazards Specific Chemicals (main entries) Appendix 1 Abbreviations Appendix 2 Fire-Related Data Appendix 3 Glossary and Technical terms Appendix 4 Index of Chemical Names and Serial Numbers Appendix 5 Index of CAS Registry Numbers.
Keywords: Chemical reactions -- Handbooks, manuals, etc.; Chemicals -- Safety measures -- Handbooks, manuals, etc.; Hazardous substances -- Handbooks, manuals, etc.; elektronické knihy; electronic books